If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11g + 3 = 12g Reorder the terms: 3 + 11g = 12g Solving 3 + 11g = 12g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-12g' to each side of the equation. 3 + 11g + -12g = 12g + -12g Combine like terms: 11g + -12g = -1g 3 + -1g = 12g + -12g Combine like terms: 12g + -12g = 0 3 + -1g = 0 Add '-3' to each side of the equation. 3 + -3 + -1g = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1g = 0 + -3 -1g = 0 + -3 Combine like terms: 0 + -3 = -3 -1g = -3 Divide each side by '-1'. g = 3 Simplifying g = 3
| -17-2a=1 | | -4+17(x)=183 | | -5x+y=-7 | | x-14=x+15 | | 9b+40=3b | | y/1/2 | | 9(2x-1)(2x-1)-8=0 | | (3x+3)(3x+3)-27=0 | | 1/2n+4=-3/2-18 | | 3x=x+25 | | x^2-6xy+5y^2-x+5y=0 | | (X-3/7)=2/3(3/2x-9/14) | | .07x+x=5000 | | 1.07x=5000 | | 17/7x=1/2 | | 4/7×x=40 | | -6x-y=-2 | | 200x^2=100 | | 7-3(2y+1)=16 | | 1.75x-0.75y=0 | | 5x^2+5x+5=100 | | 5x^2+6x+6=20 | | 4x+15y=31 | | 7x+6y=41 | | 3(0)-9(1/3)=15 | | 6x-5y=41 | | 3(3)-9(3)=15 | | 5x+2y=1.5 | | 4x-2y=-0.1 | | 1/(1-tanx) | | -9a+8a+36=11 | | 8.99x+4.6y-5.75xy=0 |